2008
DOI: 10.1038/cgt.2008.95
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HBX, an oncoprotein of hepatitis B virus, blocks reoviral oncolysis of hepatocellular carcinoma cells

Abstract: Although reovirus has been used in tests as a potential cancer therapeutic agent against a variety of cancer cells, its application to hepatocellular carcinoma cells, in which the hepatitis B virus (HBV) X (HBX) protein of HBV plays a primary role, has not yet been explored. Here, we describe experiments in which we use reovirus to treat Chang liver carcinoma cells expressing either a vector only (Chang-vec) or a vector encoding HBX protein (Chang-HBX). Although Chang-vec cells readily support reoviral prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Although several lines of evidence indicate that Ras-transformed cells are preferentially susceptible to reovirus through the inactivation of PKR phosphorylation, 2,8 we have recently found that PKR inactivation by Ras activation does not determine reovirus replication in a liver cell expressing hepatitis B virus X, an oncoprotein of the hepatitis B virus. 29 Therefore, we believe that other factors mediated by CUG2 may be involved in reovirus replication. To address this question, we examined whether CUG2 expression depends on p38 MAPK and Figure 4 Activation of Ras is required for reovirus propagation and reovirus-induced cell death.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although several lines of evidence indicate that Ras-transformed cells are preferentially susceptible to reovirus through the inactivation of PKR phosphorylation, 2,8 we have recently found that PKR inactivation by Ras activation does not determine reovirus replication in a liver cell expressing hepatitis B virus X, an oncoprotein of the hepatitis B virus. 29 Therefore, we believe that other factors mediated by CUG2 may be involved in reovirus replication. To address this question, we examined whether CUG2 expression depends on p38 MAPK and Figure 4 Activation of Ras is required for reovirus propagation and reovirus-induced cell death.…”
Section: Discussionmentioning
confidence: 96%
“…6,7 There is a strong body of evidence that Ras-transformed cells are preferentially susceptible to reovirus (type 3 Dearing strain) through inactivation of PKR (dsRNAactivated protein kinase) phosphorylation, 8,9 and activation of the oncogenic Ras-signaling pathway enhances reoviral oncolytic targeting in various types of human cancers, 10,11 although our recent study shows that other signaling pathways may also contribute to the susceptibility of a hepatic cancer cell to reoviral replication and oncolysis. 12 Reoviral efficacy has been examined in the treatment of gliomas and other cancers in immunocompetent hosts and has not been shown to produce significant toxicities. 13 These and many other results have led to the current tests of reovirus in several clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Activation of the oncogenic Ras-signaling pathway enhances reoviral oncolysis in various types of human cancers, 11,12 although our recent study shows that other signaling pathways may also contribute to the susceptibility of hepatic cancer cells to reoviral replication and oncolysis. 13 Reoviral efficacy has been examined in the treatment of gliomas in immunocompetent hosts and has not produced significant toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…However, reovirus also displays striking cytolytic activity in certain types of transformed cells (4,5). Evidence that Ras-transformed cells are preferentially susceptible to reovirus T3D (type 3 Dearling strain) via inactivation of the protective PKR (dsRNA-activated protein kinase) phosphorylation pathway has been reported (6-8) although our study has revealed that Ras activation alone does not enable reovirus to induce oncolysis in hepatocellular cacinoma cells expressing HBX, an oncoprotein of hepatitis B virus (9). Furthermore, the use of reovirus in the treatment of gliomas in immunocompetent hosts and the inoculation of reovirus into the brains of non-human primates have not produced significant toxicities (10), thereby supporting the current tests of reovirus in several clinical trials (11).…”
Section: Introductionmentioning
confidence: 43%
“…Mutations not only in the K-ras proto-oncogene but also in components of the Wnt/ß-catenin signaling pathway are frequently detected in colorectal cancers (31). Although Ras signaling plays a critical role in dictating host cell permissiveness to reovirus (6), other signaling pathways may also contribute susceptibility to reoviral replication and oncolysis (9). Since it has been reported that reovirus efficiently kills many colon cancer cell lines (12) in vitro and in a rodent model in vivo (12,14,25), we wondered whether upregulation of ß-catenin might in some way enhance reovirus replication.…”
Section: Discussionmentioning
confidence: 99%